The black ice - Connelly, Michael, 1956- (Connelly, Michael, 1956- Harry Bosch series, 2021)
When an LAPD narcotics officer is found with a fatal bullet wound and a suicide note, Detective Harry Bosch follows a bloody trail of drug murders across the Mexico border. Working the case, LAPD detective Harry Bosch is reminded of the primal police rule he learned long ago: Don't look for the facts, but the glue that holds them together. Soon Harry's making some very dangerous connections, starting with a dead cop and leading to a bloody string of murders that wind from Hollywood Boulevard to the back alleys south of the border. Now this battle-scarred veteran will find himself in the center of a complex and deadly game--one in which he may be the next and likeliest victim.